Strategi Pemberdayaan Keluarga untuk Perempuan dan Anak Korban Dampak Penyalahgunaan Narkoba Dengan Pendekatan Multidisiplin - Afrianti, Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Drug abuse not only impacts individual users, but also imposes serious consequences on families, especially women and children who are indirectly victimized. This study examines effective family empowerment strategies to assist female and child victims of substance abuse impacts through a multidisciplinary approach. The research method used was a literature study with descriptive analysis of various family empowerment programs that have been implemented in Indonesia and other countries. Study results show that effective family empowerment strategies include integrated psychosocial, economic, educational, and legal approaches. Successful empowerment programs require collaboration between social workers, psychologists, counselors, medical personnel, and local governments. The findings suggest that a multidisciplinary approach can provide a comprehensive solution to address the impact of drug abuse on families, particularly vulnerable women and children.